2012
DOI: 10.1097/01.ogx.0000422943.33743.3a
|View full text |Cite
|
Sign up to set email alerts
|

Three Postpartum Antiretroviral Regimens to Prevent Intrapartum HIV Infection

Abstract: The standard prophylactic regimen used as antiretroviral therapy (ART) for infants born to mothers in high-income and middle-income countries who are infected with human immunodeficiency virus (HIV) infection has been a 6-week course of zidovudine.Randomized controlled trials investigating postexposure prophylaxis for infants born to late-presenting women infected with HIV who did not receive ART in pregnancy have been conducted in breast-fed populations but not in nonYbreast-fed populations. Several trials sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
6
31
0
4
Order By: Relevance
“…Serious adverse events possibly related to study drugs were observed in 8.4% of infants, with higher rates in the three‐drug group than in the ZDV‐alone group or the two‐drug group. Neutropaenia and anaemia accounted for the majority of serious adverse events; in particular, grade 2 or greater neutropaenia occurred in 16.4% infants receiving only ZDV and in 15.0% of those receiving two drugs, reaching 27.0% in infants receiving three drugs ( P < 0.0001) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Serious adverse events possibly related to study drugs were observed in 8.4% of infants, with higher rates in the three‐drug group than in the ZDV‐alone group or the two‐drug group. Neutropaenia and anaemia accounted for the majority of serious adverse events; in particular, grade 2 or greater neutropaenia occurred in 16.4% infants receiving only ZDV and in 15.0% of those receiving two drugs, reaching 27.0% in infants receiving three drugs ( P < 0.0001) .…”
Section: Discussionmentioning
confidence: 98%
“…However, the optimal prophylactic regimen and the additional efficacy of CNP in reducing MTCT risk in such situations are not well understood. CNP was found to be superior to one‐drug NP in a randomized trial conducted in exclusively formula‐fed infants born to women who had not received ARVs during pregnancy , but data in other high‐risk situations are limited. Furthermore, there is some controversy regarding whether high‐risk newborns should receive therapeutic rather than prophylactic doses of ARVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In high‐risk children, perinatal prophylaxis should be initiated soon after birth and should include two or three antiretroviral drugs in order to lower the infection risk as much as possible . This approach has been proved to be effective and safe …”
Section: Hiv‐1 Infection In Children and Adolescents: False Beliefs Amentioning
confidence: 99%
“…Nielsen-Saines en el año 2012 demostró que la administración de zidovudina por seis semanas con tres dosis de nevirapina o la administración de zidovudina, lamivudina y nelfinavir por 15 días a recién nacidos, hijos de mujeres sin tratamiento antirretroviral en el embarazo o parto fue más eficaz que la zidovudina sola para reducir la transmisión intraparto del VIH al niño (2,2%, 2,4% y 4,8%, respectivamente, p = 0,046). Como los efectos adversos fueron más frecuentes con tres fármacos, la elección de zidovudina con nevirapina comenzó a utilizarse en los casos de mal control del embarazo (13,16) .…”
Section: Introductionunclassified